MANAJEMEN PEMBELAJARAN PROGRAM VOKASIONAL BAGI ANAK TUNAGRAHITA DI SLB KABUPATEN SUBANG - Sarimanah Sarimanah (WALI PIKIR : Journal of Education, 2023)
This research using analytical descriptive method through a qualitative approach. The result of this study can be described as follows: (1) Planning made by the teacher has not described how the steps undertaken in learning vocational activities. (2) The implementation of vocational program learning has not yet described the learning steps that are in accordance with the educational standard (3) The assessment made has not yet described the format of the assessment in accordance with established educational assessment standards. (4) Efforts to improve the condition of the child are still not successful because it is only taught by the teacher. The results of the study recommendations are that school should position the teacher as their performance and skill of learning, expected to further enhance on the implementation of learning, resulting in increased professionalism and teacher performance